Into the Unknown: Examining Neural Representations of Parent–Adolescent Interactions. Issue 6 (22nd July 2021) - Ratliff, Erin L.; Kerr, Kara L.; Misaki, Masaya; Cosgrove, Kelly T.; Moore, Andrew J.; DeVille, Danielle C.; Silk, Jennifer S.; Barch, Deanna M.; Tapert, Susan F.; Simmons, W. Kyle; Bodurka, Jerzy; Morris, Amanda Sheffield
Abstract : The parent–adolescent relationship is important for adolescents' emotion regulation (ER), yet little is known regarding the neural patterns of dyadic ER that occur during parent–adolescent interactions. A novel measure that can be used to examine such patterns is cross‐brain connectivity (CBC)—concurrent and time‐lagged connectivity between two individuals' brain regions. This study sought to provide evidence of CBC and explore associations between CBC, parenting, and adolescent internalizing symptoms. Thirty‐five adolescents (mean age = 15 years, 69% female, 72% Non‐Hispanic White, 17% Black, 11% Hispanic or Latino) and one biological parent (94% female) completed an fMRI hyperscanning conflict discussion task. Results revealed CBC between emotion‐related brain regions. Exploratory analyses indicated CBC is associated with parenting and adolescent depressive symptoms.